PENGARUH JUMLAH MATA TUNAS TERHADAP PERTUMBUHAN DAN HASIL BEBERAPA VARIETAS JAHE (ZINGIBER OFFICINALE L.) - S.Minardi FP UTP Ska; Setie Harieni FP UTP Ska (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta)
Low P availability observed in Andisols are considered as importantas limited factors for croping production. Hence, efforts made to improve P availabilities to crop demand are needed for management of Andisols. Quality from organic matters that are added to soils are able to improve P availability. Farm-yard manure, rice straw and Gliricidia sepium pruning are types of organic matter that are commonly applied to soil by Tawangmangu farmers of Central Java to improve crop productivity. Soil of the area is dominated by Andisols. Objectives of this study was to elucidate effects of application of the quality three types of organic matters on P availability and uptake by maize. The study was carried out in a glasshouse of the Faculty of Agriculture, Sebelas Maret University, from Agustus to Nopember 2005. This study applied the Randomized Completely Block Design with two factors. The first factor comprised four levels of organic matter input (no organic matter, manure, rice straw, and Gliricidia sepium pruning) at a rate of 10 t ha-1. The second factor comprised three levels of P fertilizer (no P addition, 50 kg P2O5 ha‑1, 100 kg P2O5 ha‑1). Maize was grown for 90 days. Gliricidia sepium pruning having highest content of humic and fulvic acids (30,31%) and C/P (74,38) played the most significant role in increasing P availability. Increased available P due to application of the three types of organic matters was in the order of Gliricidia sepium pruning (53,61%), manure (16,13%) and rice straw (1,18%) compared to control. The changes in soil chemical properties (Al, Fe and pH) and increasing P availability, increased P uptake in the tops of maize. Key words : P availability Andisol, Organic matter, Zea mays